Asymmetric hydrogen bonding in formic acid–nitric acid dimer observed by quantum molecular dynamics simulations - Chanisorn Ngaojampa (2018)
© 2017, Springer-Verlag Berlin Heidelberg. Heterodimer of formic acid and nitric acid, of which the monomer acidity has large difference, was studied by on-the-fly ab initio molecular dynamics (AIMD) and path integral molecular dynamics (PIMD) simulations with RI-BVWN/SVP level of density functional theory, to elucidate the nuclear quantum effect and isotopic effect on the structural dynamics of the heterodimer. At 300 K, the two hydrogen bonds were maintained in both AIMD and PIMD regimes. Analyses in structural parameters suggested that this heterodimer should exist in the asymmetric binding mode, where hydrogen bonding is stronger on the C=O…H–O–N side. The asymmetry in the binding can be observed even more when the nuclear quantum effect was introduced. Although the complex has an equal conformation connected by a double hydrogen bonding, analyses in the principal component modes revealed the dominance of the dimer opening and twisting motions, which were suggested to obstruct double-proton transfer.